2008
DOI: 10.1007/s12010-008-8306-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Solid Concentration on Enzymatic Hydrolysis and Fermentation of Steam-Exploded Corn Stover Biomass

Abstract: Steam-exploded corn stover biomass was used as the substrate for fed-batch separate enzymatic hydrolysis and fermentation (SHF) to investigate the solid concentration ranging from 10% to 30% (w/w) on the lignocellulose enzymatic hydrolysis and fermentation. The treatment of washing the steam-exploded material was also evaluated by experiments. The results showed that cellulose conversion changed little with increasing solid concentration, and fermentation by Saccharomyces cerevisiae revealed a nearly same etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
73
6
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 25 publications
15
73
6
7
Order By: Relevance
“…Shorter hydrolysis times were required for low substrate loadings as compared to longer hydrolysis times for high substrate loading, which was in agreement to reported work on CMC and corn stover using cellulase (Al-Zuhair 2008; Lu et al 2010). This may be due to high initial viscosity at high substrate loadings which poses mass transfer limitations, resulting in a low conversion efficiency (Ioelovich and Morag 2012;Lu et al 2010;Mussatto et al 2008;Sarkar and Etters 2004). End-product inhibition on cellulases by cellobiose was avoided by supplementing b-glucosidase using Novozyme 188 (Teeri 1997).…”
Section: Effect Of Substrate Loadingsupporting
confidence: 90%
See 3 more Smart Citations
“…Shorter hydrolysis times were required for low substrate loadings as compared to longer hydrolysis times for high substrate loading, which was in agreement to reported work on CMC and corn stover using cellulase (Al-Zuhair 2008; Lu et al 2010). This may be due to high initial viscosity at high substrate loadings which poses mass transfer limitations, resulting in a low conversion efficiency (Ioelovich and Morag 2012;Lu et al 2010;Mussatto et al 2008;Sarkar and Etters 2004). End-product inhibition on cellulases by cellobiose was avoided by supplementing b-glucosidase using Novozyme 188 (Teeri 1997).…”
Section: Effect Of Substrate Loadingsupporting
confidence: 90%
“…The results for reducing sugars showed that at higher substrate loadings, the initial rate of reaction was faster, hence the higher production of sugars in agreement with Gan et al (2003). Shorter hydrolysis times were required for low substrate loadings as compared to longer hydrolysis times for high substrate loading, which was in agreement to reported work on CMC and corn stover using cellulase (Al-Zuhair 2008; Lu et al 2010). This may be due to high initial viscosity at high substrate loadings which poses mass transfer limitations, resulting in a low conversion efficiency (Ioelovich and Morag 2012;Lu et al 2010;Mussatto et al 2008;Sarkar and Etters 2004).…”
Section: Effect Of Substrate Loadingsupporting
confidence: 87%
See 2 more Smart Citations
“…The particle size of rice straw and silvergrass inversely influenced the acetic acid formation in dilute acid pretreatment (Guo et al, 2008); however, it was not confirmed in this study. The acetic acid concentration was lower than dilute acid Hodge et al, 2008), formic acid (Xu et al, 2009a), lime , alkali ), hydrothermal pretreatment (脰hgren et al, 2006;Lu et al, 2010) of corn stover; compared to other feedstocks listed in the table. NaOH has higher reactivity with hemicellulose than cellulose due to amorphous characteristics of hemicellulose (Lai, 2001).…”
Section: Byproducts Formationmentioning
confidence: 90%